2004
DOI: 10.1016/j.molbiopara.2003.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Human serum haptoglobin is toxic to Plasmodium falciparum in vitro

Abstract: Innate immune responses are important in the control of malaria, particularly in those who have not yet mounted an effective adaptive response. Here we report that the human serum acute phase protein, haptoglobin is toxic to Plasmodium falciparum cultured in vitro. This effect is phenotype-dependent and occurs during the trophozoite phase of the asexual life cycle. We propose that the increased levels of haptoglobin seen in the acute phase response may be protective against malaria in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The roles of the SPHs that do not contain a clip domain are, however, much less well studied. The known ones include mammalian haptoglobin, which regulates Langerhans cell function and is toxic to Plasmodium trophozooites (36)(37)(38); the hepatocyte growth factor that suppresses dendritic cell function (39,40); and the human neutrophil granule protein, azurocidin, which has both signaling and antimicrobial activity (41). In insects, in addition to SPH-3, the two non-clip domain SPHs suggested to play immune roles are an azurocidin-like protein in Trichoplusia ni (another lepidopteran) (40) and ISP15 in the mosquito Anopheles gambiae (41).…”
Section: Discussionmentioning
confidence: 99%
“…The roles of the SPHs that do not contain a clip domain are, however, much less well studied. The known ones include mammalian haptoglobin, which regulates Langerhans cell function and is toxic to Plasmodium trophozooites (36)(37)(38); the hepatocyte growth factor that suppresses dendritic cell function (39,40); and the human neutrophil granule protein, azurocidin, which has both signaling and antimicrobial activity (41). In insects, in addition to SPH-3, the two non-clip domain SPHs suggested to play immune roles are an azurocidin-like protein in Trichoplusia ni (another lepidopteran) (40) and ISP15 in the mosquito Anopheles gambiae (41).…”
Section: Discussionmentioning
confidence: 99%
“…22 The effect of Hp concentration on the risk of severe malaria is also not known. Hp was toxic to malaria parasites in vitro, 23 and increased parasite burden was demonstrated in an Hp knockout mouse. 24 The A-61C single nucleotide polymorphism (SNP) in the Hp promoter region, which causes very low Hp concentrations, 25,26 was associated with a reduced risk of uncomplicated malaria.…”
Section: Introductionmentioning
confidence: 99%
“…4 Hp is directly toxic to Plasmodium falciparum in vitro at concentrations that may occur during an acute-phase response. 5 The exact mechanism of action is not known. Hp does not enter the infected erythrocyte but may act indirectly, disrupting normal parasite protein trafficking within the host cell.…”
Section: Introductionmentioning
confidence: 99%
“…Hp does not enter the infected erythrocyte but may act indirectly, disrupting normal parasite protein trafficking within the host cell. 5 An in vivo model of malaria infection has demonstrated that parasite burdens and peak parasite densities were higher in Hp knockout mice. 6 In addition, Hp is also antimicrobial; it makes iron unavailable to bacteria using Hb, (e.g., Escherichia coli) and causes agglutination of Streptococcus pyogenes.…”
Section: Introductionmentioning
confidence: 99%